Visceral and subcutaneous fat in patients treated with olanzapine: a case series - Gilles, Maria; Hentschel, Frank; Paslakis, Georgios; Glahn, Eva Valerie; Lederbogen, Florian; Deuschle, Michael (Clinical neuropharmacology, 2010)
Objectives: - We hypothesized that olanzapine may contribute to visceral adiposity, a core symptom of metabolic syndrome. - Methods: - Using computed tomography, we examined the effect of olanzapine on visceral and subcutaneous fat distribution, body mass index, fasting glucose, and lipids in an unselected population of 14 schizophrenic patients. - Results: - We found a 6-week olanzapine treatment to be related to increased body mass index and proportion of total fat at the level of the fourth vertebral body. - Conclusions: - On the basis of these findings, we conclude that weight gain after a 6-week olanzapine treatment is partly attributable to increased visceral fat and may thus contribute to metabolic syndrome.
Gesehen am 15.10.2020